p-harmonic functions in metric spaces - Farnana, Zohra (The Libyan Journal of Science, 2022)
The main object of this paper is to present the p-harmonic functions in metric spaces and compare them with the harmonic functions in the Euclidean spaces. We obtain many useful properties for the p-harmonic functions in metric spaces. In particular the p-harmonic functions in metric spaces satisfy the strong maximum principle, the Harnack's inequality and are locally Hölder continuous.